Prefixation in medieval literary Galician - López Viñas, Xoán (Madrygal. Revista de Estudios Gallegos, 2014)
This article explores the presence of prefixation in medieval Galician, based on a selection of literary texts. The first section offers a brief description of the concept of prefixation, before moving on, in section two, to examine and assess the types of prefixation used in the different word-formation processes (derivation, compounding, mixed). The final part of the study looks at the prefixal system in medieval literary Galician..
Keywords: prefixation; derivation; compounding; prefix; affix; medieval Galician.